Memória de mulheres ucranianas: recriação de tradições em Prudentópolis Paraná - Tenchena, Sandra Mara (2010)
This dissertation deals with the memory of women descendants of Ukrainian living in Prudentópolis, country side of Paraná, and peculiar aspect is the fact that its population consists majorly from Ukrainians . There, traditions and religious festivals keep alive the Ukrainian culture. This led me to know the different ways of appropriation of the specific symbolical tissues of this culture, through gender s clipping associated to specificities of generations responsible by production of own meanings systems this culture. For all this, I resorted to studies of memory through authors as: Brandão (1985), Pollak (1989), Nora (1993), Bosi (1994), Halbwachs (2004), among others that have addressed this problem associating memory to its literary dimension, historical, socio-cultural. The Ukrainians, an important group of immigrants who migrated to Paraná as free workers at the beginning of the 20th century, built important activities for the region's cultural life and to the local economy. They shared their lives with immigrant Pollack s, Italians and Germans, building a strengthened segment of cultural hybridization of own history of Brazil. The choice of ethnographic approach, which not only could describe the culture and traditions, but also the history and socio-economical transformations of Prudentópolis town, in the State of Paraná, aimed to interpret the senses and meanings of actions turned to the assertion, resistance and identification of its population. For that, I resorted to the systematic searching exercise with my observing participation of rites and customs paying so familiar to recover traditional customs, intending to recuperate traditional habits, seeking to produce, initially, an Ethnography that could express, with refinement of details, the ways of living of women and the Ukrainians. The methodology was based on qualitative research because of their importance for studies of complex interpretative phenomenal and by the possibility of immersion on the context and reality of the environment researched. By registration of Prudentópolis daily s life, such as analyzing the history of these women lives, by memorizing as methodological resource, establishing relations by their memories identities formulations. I looked for, by this essay, tried to understand the importance of Ukrainian Women on the preservation of theirs cultural traditions